Strategy of didactic supervision of the baseball coach in the sports initiation (Original) (Revista científica Olimpia, 2020)
The research presented studies the professional improvement of Baseball coaches of the Sub 12 years category, the same part of determining the inadequacies that are manifested in the didactic work of the Baseball coach who works in the initiation sport with students of the Sub 12 years category. Its solution takes place within the framework of the process of professional improvement of the Baseball coach, specifying the professional improvement in attention to the didactic of the Baseball coach, the research proposes the development of a strategy of professional improvement in attention to the didactic, for Baseball coaches who work in the sport of initiation in the Sub 12 years’ category. The results obtained demonstrate, on the one hand, the theoretical gaps existing in the scientific literature consulted on professional improvement in the sports field and on the other the lack of a didactic-methodological conception that privileges ways, ways and methods of overcoming consistent with the needs Professionals of the coaches who work in Baseball, sub twelve years of sports initiation category.
Keywords: professional improvement, baseball coach, didactic preparation, baseball teaching-learning process, sports initiation